Phonological deviations of Indonesian-speaking adolescents with Down syndrome: a case study - Nandita Wana Putri,; Sarwiji Suwandi,; Andayani, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates phonological deviations in Indonesian-speaking adolescents with down syndrome, addressing a significant gap in cross-linguistic research on phonological development in down syndrome populations. While extensive studies exist in various languages, research in Indonesian remains limited. The study employed a qualitative case study approach, examining six Indonesian-speaking adolescents with down syndrome (aged 13-15 years) at Special Needs School of Surakarta. Data collection involved interviews, observations, and documentation. Furthermore, researchers made direct observations of the subject and recorded the speech of adolescents with down syndrome during the learning process in the classroom. The data analysis technique focused on the recording of language utterances produced by adolescents with down syndrome. The results revealed three main patterns of phonological deviations: phoneme omission, substitution, and cluster reduction. The dominant pattern was phoneme omission through apheresis (phoneme omission at word beginnings). A consistent pattern of phoneme substitution was observed, particularly the replacement of apicoalveolar /n/ with dorsovelar /ŋ/, reflecting articulatory compensation strategies. Variations in vowel and consonant omissions demonstrated heterogeneity in phonological deviations among participants. Further, the unique case of NT who despite experiencing complex deviations, demonstrated higher language production. This research contributes to the understanding of phonological patterns in down syndrome adolescents and reinforces the significance of considering both anatomical constraints and environmental factors in developing effective intervention strategies for speech and language development in this population.